Interrelation between Cross-Border Cooperation (CBC) and Social Capital: Conceptual Framework - Dvalishvili, Tinatini (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2019)
This article tracks the definitional debates on social capital to demonstrate the many-sided nature of it. Referring to the relational nature of social capital, this paper regards it as an output of cross-border cooperation. The basis of social capital is social interaction, and cross-border cooperation facilitates and reinforces it in equal measure across national borders. Therefore, this article considers cross-border cooperation as one way to generate formal/informal, linking, bonding, bridging, transnational and other varieties of social capital.